2018
DOI: 10.1097/sla.0000000000002648
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Division Versus Nondivision of Short Gastric Vessels During Nissen Fundoplication

Abstract: Although laparoscopic Nissen fundoplication has durable efficacy for heartburn symptom control at up to 20 years follow-up, division of short-gastric vessels failed to confer any reduction in side effects, and was associated with persistent epigastric bloat symptoms at late follow-up in this trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…High rates of dysphagia are reported shortly after surgery, possibly due to oedema at the gastro‐oesophageal junction . However, at long‐term follow‐up, dysphagia rates in our cohort were low, being only 3–6%, which is in line with other studies . Bloating, flatulence and inability to belch are more commonly reported, with rates up to 50% .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…High rates of dysphagia are reported shortly after surgery, possibly due to oedema at the gastro‐oesophageal junction . However, at long‐term follow‐up, dysphagia rates in our cohort were low, being only 3–6%, which is in line with other studies . Bloating, flatulence and inability to belch are more commonly reported, with rates up to 50% .…”
Section: Discussionsupporting
confidence: 89%
“…Bloating, flatulence and inability to belch are more commonly reported, with rates up to 50% . Although such inconvenience does not seem to depend on the type of fundoplication performed, a recent study showed that the division of the short gastric vessels significantly increased the frequency of bloating …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations